Effects of thermal annealing on the distribution of boron and phosphorus in p-i-n structured silicon nanocrystals embedded in silicon dioxide. (26th November 2021) - Nomoto, Keita; Cui, Xiang-Yuan; Breen, Andrew; Ceguerra, Anna V; Perez-Wurfl, Ivan; Conibeer, Gavin; Ringer, Simon P
Abstract: Thermal annealing temperature and time dictate the microstructure of semiconductor materials such as silicon nanocrystals (Si NCs). Herein, atom probe tomography (APT) and density functional theory (DFT) calculations are used to understand the thermal annealing temperature effects on Si NCs grown in a SiO2 matrix and the distribution behaviour of boron (B) and phosphorus (P) dopant atoms. The APT results demonstrate that raising the annealing temperature promotes growth and increased P concentration of the Si NCs. The data also shows that the thermal annealing does not promote the incorporation of B atoms into Si NCs. Instead, B atoms tend to locate at the interface between the Si NCs and SiO2 matrix. The DFT calculations support the APT data and reveal that oxygen vacancies regulate Si NC growth and dopant distribution. This study provides the detailed microstructure of p-type, intrinsic, and n-type Si NCs with changing annealing temperature and highlights how B and P dopants preferentially locate with respect to the Si NCs embedded in the SiO2 matrix with the aid of oxygen vacancies. These findings will be useful towards future optoelectronic applications.